2020
DOI: 10.1177/0038026120962671
|View full text |Cite
|
Sign up to set email alerts
|

Class, affective labour and exploitation: Unemployment and the creation of work on the margins

Abstract: This article examines the articulation of class and affective labour in the creation of work for the unemployed. Bringing together two sets of interlinking literature on work, class and subjectivity – the proliferating and increasingly popular literature on affective labour and the highly influential Bourdieusian inspired sociologies of class – we argue for closer research attention to the specificities of exploitation in contemporary experiences of paid employment. To do this, we draw on in-depth research on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This has been a key focus of feminist critiques of immaterial labour, which have observed that this 'new' economy nevertheless relies on the exploitation of longstanding forms of feminised labour (Bolton, 2009;Oksala, 2016) and that young women experience heightened forms of insecurity and specific manifestations of class inequality in immaterial economies that tend to be highly precarious (Gill & Pratt, 2008). In response, there is now an emerging literature which is focusing on the way that class inequalities operate in immaterial economies (Gerrard, 2019;Gerrard & Farrugia, 2021). In this article we contribute to this literature by drawing on the tradition of class theorising established in feminist developments of Bourdieu (Adkins & Skeggs, 2005;Lawler, 2005;Skeggs, 2004;Skeggs & Loveday, 2012).…”
Section: Class and New Forms Of Labourmentioning
confidence: 99%
“…This has been a key focus of feminist critiques of immaterial labour, which have observed that this 'new' economy nevertheless relies on the exploitation of longstanding forms of feminised labour (Bolton, 2009;Oksala, 2016) and that young women experience heightened forms of insecurity and specific manifestations of class inequality in immaterial economies that tend to be highly precarious (Gill & Pratt, 2008). In response, there is now an emerging literature which is focusing on the way that class inequalities operate in immaterial economies (Gerrard, 2019;Gerrard & Farrugia, 2021). In this article we contribute to this literature by drawing on the tradition of class theorising established in feminist developments of Bourdieu (Adkins & Skeggs, 2005;Lawler, 2005;Skeggs, 2004;Skeggs & Loveday, 2012).…”
Section: Class and New Forms Of Labourmentioning
confidence: 99%
“…I argue that we must assess the nature of everyday relationships at work to understand the emotional malleability of solidarity as an ongoing process and the varied ways in which dock workers and their families experienced and expressed it. I also intend that this article provides historical context to contemporary studies of the emotions of class, and precarity in particular, to illustrate how the emotions of solidarity functioned and continue to function as a form of resistance (Gerrard & Farrugia, 2021;Patulny et al, 2020). These emotions have always been rooted in converging structures of power such as class, gender and race (Connell, 2005;Skeggs, 1997;Virdee, 2014).…”
mentioning
confidence: 99%